Child bride : the untold story of Priscilla Beaulieu Presley - Finstad, Suzanne, 1955- (New York : Harmony Books, 1997)
You could say that fate placed Elvis Presley, the most famous GI in the army, in Germany, and that fate, too, played a role in Priscilla Beaulieu's family's transfer to that same country in that same year. But that's where fate leaves off and sheer resolve takes over, as a beautiful fourteen-year-old girl determines to meet the twenty-six-year-old King of Rock and Roll - and the rest is truly history. Child Bride is the never-before-told story of Elvis's love affair with
Includes bibliographical references (p. [371]-381) and index.
Keywords: Presley, Priscilla Beaulieu; Motion picture actors and actresses -- United States -- Biography